'After they finish their meals, I have my meal from the leftovers; I have to adjust:" Examining How Gender Norms Affect Anemia Rates in Odisha India (P04-122-19). (13th June 2019) - Sedlander, Erica; Ladwa, Chandni; Talegawkar, Sameera; Ganjoo, Rohini; Rimal, Rajiv
Abstract: Objectives: Half of women of reproductive age in India have iron deficiency anemia compared to only 23% of men. Most research focuses on biological reasons for this discrepancy and access to iron-folic acid and iron-rich foods. However, recent research in India shows that inequitable gender norms may affect a woman's ability or desire to take iron supplements and to eat iron-rich food. The objective of this study is to examine how and why gender norms may be affecting high and persistent rates of anemia in India. Methods: We conducted 25 key informant interviews and 16 focus group discussions with women of reproductive age, adolescents, husbands and mothers-in-law ( n  = 148) in Odisha, India. We purposively sampled key informants and randomly sampled focus group participants. We analyzed the data using applied thematic analysis in Nvivo software. Results: Our data shows that unequal gender norms impact behaviors that are directly related to high rates of anemia. Women are often serving their husband, children, and in-laws first and "adjusting" to whatever is leftover which may be poor in nutritional qualities and less iron rich. Men are also the main breadwinners but often spend their money on alcohol, money that could be spent on iron-rich food for the household. Women reported that extreme fatigue is a normal part of being a woman and that a woman's plight is to take care of her family at any cost. Given that fatigue, the primary symptom of anemia is normalized; women may be less likely to seek treatment. Women tend to prioritize the health of their family over her own which could affect her ability or desire to go to the health center to get tested for anemia or to obtain iron supplements. Pregnant women are more likely to take iron supplements for the health of the baby, not her own health. While non-pregnant women of reproductive age who were not diagnosed with anemia were not focused on preventive health, only major illnesses and thus, were not taking supplements at all. Conclusions: More upstream barriers, like gender norms, may be impinging on a woman's ability to take iron folic acid and to eat iron rich foods. Understanding how gender norms contribute to anemia could change the narrative from a biomedical issue to a social justice issue. Funding Sources: The Bill and Melinda Gates Foundation. Supporting Tables, Images and/or Graphs: